Ionic liquid interface at an electrode: simulations of electrochemical properties using an asymmetric restricted primitive model. (23rd January 2018) - Lu, Hongduo; Nordholm, Sture; Woodward, Clifford E; Forsman, Jan
Abstract: We use Monte Carlo simulations of a coarse-grained model to investigate structure and electrochemical behaviours at an electrode immersed in room temperature ionic liquids (RTILs). The simple RTIL model, which we denote the asymmetric restricted primitive model (ARPM), is composed of monovalent hard-sphere ions, all of the same size, in which the charge is asymmetrically placed. Not only the hard-sphere size ( d ), but also the charge displacement ( b ), is identical for all species, i.e. the monovalent RTIL ions are fully described by only two parameters ( d, b ). In earlier work, it was demonstrated that the ARPM can capture typical static RTIL properties in bulk solutions with remarkable accuracy. Here, we investigate its behaviour at an electrode surface. The electrode is assumed to be a perfect conductor and image charge methods are utilized to handle polarization effects. We find that the ARPM of the ionic liquid reproduces typical (static) electrochemical properties of RTILs. Our model predicts a declining differential capacitance with increasing temperature, which is expected from simple physical arguments. We also compare our ARPM, with the corresponding RPM description, at an elevated temperature (1000 K). We conclude that, even though ion pairing occurs in the ARPM system, reducing the concentration of 'free' ions, it is still better able to screen charge than a corresponding RPM melt. Finally, we evaluate the option to coarse-grain the model even further, by treating the fraction of the ions that form ion pairs implicitly, only through the contribution to the dielectric constant of the corresponding dipolar (ion pair) fluid. We conclude that this primitive representation of ion pairing is not able to reproduce the structures and differential capacitances of the system with explicit ion pairs. The main problem seems to be due to a limited dielectric screening in a layer near the electrode surface, resulting from a combination of orientational restrictions and a depleted dipole density.